Influence of Light on Seed Germination of Calamus manan - Mohamad, Aminuddin; Mohd. Said, Siti Hasanah (1990)
Freshly collected seeds of calamus manan were sown under three different light conditions : a)in the open b)under moderate shade of " attap" roofing and c)under intact forest canopy. At 2 , 4 and 6 month intervals, the sample that had been sown under shade (b) and (c)were moved into the open. Germination under all treatment occured percentage achieved 50% by about 6 weeks. Under forest the cumulative germination percentage did not reach 50%. The result indicate that although the seed appear insensitive to light regimes for germination some amount of light ( attap conditions ) optimize germination of Calamus manan.